GENDER DIFFERENCIES IN RESULTS OF OFF-PUMP MYOCARDIAL REVASCULARIZATION SURGERY - I. M. Sharipov; R. R. Yarbekov; A. A. Ismatov; M. M. Muradov; S. KH. Omonov; T. Z. Vakhidov (Евразийский Кардиологический Журнал, 2019)
On-pump myocardial revascularization operations in female sex patients are considered more risky in connection with anatomo-physiological peculiarities of the latter. Very little is known about the results of off-pump myocardial revascularization operations in this group of patients. Aims of the study. The purpose of the work is to study the results of off-pump myocardial revascularization in female patients.